2006
DOI: 10.1161/01.res.0000248184.21644.20
|View full text |Cite
|
Sign up to set email alerts
|

Cellular Mechanism Through Which Parathyroid Hormone–Related Protein Induces Proliferation in Arterial Smooth Muscle Cells

Abstract: Abstract-Parathyroid hormone-related protein (PTHrP) is present in vascular smooth muscle (VSM), is markedly upregulated in response to arterial injury, is essential for normal VSM proliferation, and also markedly accentuates neointima formation following rat carotid angioplasty. PTHrP contains a nuclear localization signal (NLS) through which it enters the nucleus and leads to marked increases in retinoblastoma protein (pRb) phosphorylation and cell cycle progression. Our goal was to define key cell cycle mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
20
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(28 citation statements)
references
References 43 publications
8
20
0
Order By: Relevance
“…(18) Consequently, PTHrP inhibition of the expression of p27 can promote the proliferation of vascular smooth muscle. (17) Our studies show that a similar mechanism may occur in vivo with respect to skeletal growth and development and osteoblastic bone formation. Nevertheless, a limitation of our study is that the use of a global knockout of p27 and of a model of global ablation of the NLS and C-terminus of PTHrP does not preclude the fact that indirect regulation of PTHrP action may still occur in the p27-/-Pthrp KI mouse model we have used.…”
Section: Discussionsupporting
confidence: 62%
See 2 more Smart Citations
“…(18) Consequently, PTHrP inhibition of the expression of p27 can promote the proliferation of vascular smooth muscle. (17) Our studies show that a similar mechanism may occur in vivo with respect to skeletal growth and development and osteoblastic bone formation. Nevertheless, a limitation of our study is that the use of a global knockout of p27 and of a model of global ablation of the NLS and C-terminus of PTHrP does not preclude the fact that indirect regulation of PTHrP action may still occur in the p27-/-Pthrp KI mouse model we have used.…”
Section: Discussionsupporting
confidence: 62%
“…(17) In view of our finding of upregulated p27 in skeletal tissue of Pthrp KI mice, we next determined whether the cell cycle inhibitor p27…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3G-J). Recently, it is reported that PTHrP translocates into the nucleus and functions in an intracrine manner, which is associated with altered cell-cycle progression and protection from apoptosis [15][16][17]. We noted nuclear localization of PTHrP in addition to a cytoplasmic signal; however, PTHrP may not participate in apoptotic pathways in OSCC, since we found no cleaved Caspase-3, -9, or PARP in cells deficient in PTHrP (data not shown).…”
Section: Discussionmentioning
confidence: 42%
“…The nuclear presence of PTHrP appears to trigger pRb phosphorylation and release of G 1 /S arrest and thereby cell cycle progression (21). In this setting, cyclin E/Cdk-2 kinase activity is markedly increased by PTHrP as a result of marked PTHrP-induced proteasomal degradation of p27 kip1 (47). In contrast, we show here that in Pthrp KI cells, one consequence of the absence of nuclear PTHrP action in vivo is increased p21 levels, which in turn would lead to inhibition of cyclin E/Cdk2 and cyclin D1/Cdk4/Cdk6 activities (shown to be reduced in our studies) and to cell-cycle arrest in G 1 phase.…”
Section: Modulation Of Cell Cycle and Apoptosis By Pthrpmentioning
confidence: 99%